Adverse events in a chiropractic spinal manipulative therapy single-blinded, placebo, randomized controlled trial for migraineurs. (June 2017) - Chaibi, Aleksander; Benth, Jūratė Šaltytė; Tuchin, Peter J.; Russell, Michael Bjørn
Abstract: Background: Unlike pharmacological randomized controlled trials (RCTs), manual-therapy RCTs do not always report adverse events (AEs). The few manual-therapy RCTs that provide information on AEs are frequently without details, such as the type and-, severity of the AE and reason for withdrawal. Objective: To prospectively report all AEs in a chiropractic spinal manipulative therapy (CSMT) RCT. Design: A prospective 3-armed, single-blinded, placebo, RCT. Methods: Seventy migraineurs were randomized to the CSMT or a placebo, with 12 intervention sessions over three months. The recommendations by CONSORT and the International Headache Society's Task Force on AEs in migraine RCTs were followed. A standardized reporting scheme designed for pharmacological RCTs was used, and the AEs were described as frequencies and percentages within each group. The 95% confidence intervals (CIs) for the percentages (absolute risk) of AEs in each group were calculated when possible. Attributable risk (%) and relative risk were calculated with the corresponding 95% CIs. Results: AEs were assessed in 703 sessions, with 355 in the CSMT group and 348 in the placebo group. Local tenderness was the most common AE, reported by 11.3% and 6.9% of the CSMT group and the placebo group, respectively, and tiredness on the intervention day was reported by 8.5% and 1.4% of CSMT group and the placebo group, respectively. The highest attributable risk was for tiredness on the treatment day, 7.0% (CI 3.9–10.2%) which presented a relative risk of 5.9 (CI 2.3–15.0). Conclusions: AEs were mild and transient, and severe or serious AEs were not observed. Highlights: Manual-therapy RCTs do not always report adverse events (AEs) in contrast to pharmacological RCTs. This is the first prospective manual-therapy 3-armed single-blinded placebo RCT reporting all AEs for migraineurs. Local tenderness, tiredness and neck pain were the most common AEs. No severe or serious AE were reported. We observed fewer AEs in our study than what is reported in prophylactic migraine RCTs such as topiramate, metoprolol or candesartan.